2016
DOI: 10.1002/elan.201600565
|View full text |Cite
|
Sign up to set email alerts
|

Novel Enzymatic Potentiometric Approaches for Surfactant Analysis

Abstract: 1IntroductionSurfactants form au nique class of organic compounds which generally consist of ah ydrophilic head group and ah ydrophobic chain (or tail) [1].T he hydrophobic part is usually hydrocarbon chain (C 8 -C 18 ), while the hydrophilic group may be carboxylates,s ulfates, sulfonates (anionic), polyoxyethylenated chains (nonionic) or quaternary ammoniums alts in case of cationic surfactants [1][2][3].Thew orldwide production of surfactants was about 13 million metric tonsi n2 008;7 0% of them represent a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…As this compound is composed of a hydrophobic cation and anion, it does not seem to possess ion-exchanger properties and so its function is unclear, other than decreasing the resistance of the membrane phase. Khaled et al demonstrated an enzymatic approach for surfactant analysis . As the surfactants are known to inhibit the activity of some cholinesterase enzymes, the authors used this characteristic to determine the surfactant concentration.…”
Section: Analytical Applications and Methodologiesmentioning
confidence: 99%
See 1 more Smart Citation
“…As this compound is composed of a hydrophobic cation and anion, it does not seem to possess ion-exchanger properties and so its function is unclear, other than decreasing the resistance of the membrane phase. Khaled et al demonstrated an enzymatic approach for surfactant analysis . As the surfactants are known to inhibit the activity of some cholinesterase enzymes, the authors used this characteristic to determine the surfactant concentration.…”
Section: Analytical Applications and Methodologiesmentioning
confidence: 99%
“…Khaled et al demonstrated an enzymatic approach for surfactant analysis. 187 As the surfactants are known to inhibit the activity of some cholinesterase enzymes, the authors used this characteristic to determine the surfactant concentration. The enzymatic activity of acetylcholinesterase was measured by monitoring the hydrolysis of acetylcholine with a disposable acetylcholine potentiometric sensor.…”
Section: Analytical Chemistrymentioning
confidence: 99%
“…Starting from chemical warfare detection [ 12 , 13 ], AChE biosensors have found a large application in the determination of organophosphate and carbamate pesticides inhibiting enzymes [ 14 , 15 , 16 ]. Due to a wide variety of species exerting the anticholinesterase effect, AChE biosensors were proposed as indicators of general pollution of the environment [ 17 ] and for detection of heavy metals [ 18 ], surfactants [ 19 ], fluorides [ 20 ] and organic solvents [ 21 , 22 ] exerting a non-specific inhibitory effect. Recently, AChE biosensors were also successfully utilized for the determination of reversible inhibitors, e.g., anti-dementia drugs [ 23 , 24 ] and aflatoxins [ 25 , 26 ].…”
Section: Introductionmentioning
confidence: 99%